Factors affecting sexual-self-esteem among Iranian women - Sahar Safshekan; Zahra Bostani Khalesi (Elsevier, 2024)
Introduction: The quality of marital relationships is positively impacted by women's sexual self-esteem. This study aims to determine the factors that affect sexual self-esteem among Iranian women. Methods: A total of 1176 eligible women who have been referred to comprehensive healthcare centers of Rasht, participated in this analytical cross-sectional study. A stratified two-stage cluster sampling methodology was applied to achieve samples. Data were collected using a validated Persian version of the Sexual Self-Esteem Inventory in Women-Short Form and related factors checklist. Results: The mean sexual self-esteem score of the respondents was 103.97(SD =5.29) in this study. Education level of the woman (B = 2.622, P < 0.032), employment status of the woman (B= 9.24, P < 0.01), duration of the marriage (B = 11.47, P < 0.01), body image (B = 3.446, P < 0.01), childhood sexual abuse experiences (B = −0.363, P < 0.01), was related with sexual self-esteem. The sexual self-esteem score increased with an increase in higher levels of education, employment of women, an increase in the duration of the marriage, and a positive body image. However, there was an inverse relationship between the experience of childhood sexual abuse and sexual self-esteem. Conclusions: The findings revealed that sexual self-esteem in women is influenced by background, intrapersonal, and interpersonal factors that should be approached in education, counseling, and therapy.